Characteristics of Dielectric Barrier Discharge Reactor for Material Treatment - Kostov, K. G. [UNESP]; Honda, Roberto Yzumi [UNESP]; Alves, L. M. S. [UNESP]; Kayama, M. E. [UNESP] (Soc Brasileira Fisica, 2009)
This work reports the development of atmospheric pressure plasma reactor with dielectric barrier discharge DBD for material treatment. The DBD discharge has been generated in planar geometry reactor powered by ac voltage provided by conventional high voltage transformer. The dielectric barrier consisted of two glass slabs, which cover both reactor electrodes. The air discharge gap between the dielectric layers was varied from 1.0 to 3.0mm. The power consumption of the DBD reactor was evaluated by the Lissajous figures method. The optimization of reactor geometry for material processing is discussed.
Keywords: DBD discharge; Plasma reactor; Electric circuit model